2010
DOI: 10.1055/s-0030-1258364
|View full text |Cite
|
Sign up to set email alerts
|

3-(Dichloroacetyl)chromone; A New Building Block for the Synthesis of Formylated Purine Isosteres: Design and Synthesis of Fused α-(Formyl)pyridines

Abstract: The first synthesis of 3-(dichloroacetyl)chromone from 3-(dimethylamino)-1-(2-hydroxyphenyl)propen-1-one and dichloroacetyl chloride is described. The reaction of electron-rich aminoheterocycles with 3-(dichloroacetyl)chromone provides a set of diverse fused pyridines bearing the CHCl 2 -substituent at the a-position of the pyridine core. Subsequent hydrolysis leads to the formation of annulated a-(formyl)pyridines.Purine isosteres and purine-like scaffolds are of considerable interest as major privileged scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Our starting point was the development of suitable conditions for the synthesis of pyrido[3,2‐ c ]coumarin 3a by reaction of chromone‐3‐carboxylic acid 1a with aminopyrazole 2a (Scheme ). The aminopyrazole 2a and related aminoheterocycles used in this study were prepared as previously reported in our work related to the synthesis of heteroannulated pyridines, spirocyclic 1,4‐dihydropyridine compounds, and 3,4‐fused coumarins . The best yield of 3a (up to 90 %) was obtained under the conditions reported in entry 5 of Table using acetic acid as solvent (14 h, 60 °C).…”
Section: Resultsmentioning
confidence: 89%
“…Our starting point was the development of suitable conditions for the synthesis of pyrido[3,2‐ c ]coumarin 3a by reaction of chromone‐3‐carboxylic acid 1a with aminopyrazole 2a (Scheme ). The aminopyrazole 2a and related aminoheterocycles used in this study were prepared as previously reported in our work related to the synthesis of heteroannulated pyridines, spirocyclic 1,4‐dihydropyridine compounds, and 3,4‐fused coumarins . The best yield of 3a (up to 90 %) was obtained under the conditions reported in entry 5 of Table using acetic acid as solvent (14 h, 60 °C).…”
Section: Resultsmentioning
confidence: 89%
“…We prepared a series of 3‐methoxalylchromones 1a – d , 3‐aroylchromones 2a – h , and 3‐cinnamoylchromone 3 starting from readily accessible 3‐(dimethylamino)‐1‐(2‐hydroxyaryl)prop‐2‐en‐1‐ones by using a one‐pot acylation procedure (Table ) , , . Almost all the chromones used in this study were reported and described in our previous work , …”
Section: Resultsmentioning
confidence: 99%
“…The reaction of 2-amino-cyanopyrrols 10a-c with 50 afforded pyrrolo [2,3-b]pyridines 53a-c in very good yield and with very good regioselectivity (Scheme 25). 40 The products are formed by the same mechanism as discussed for the formation of product 52 (Scheme 23). Reflux of a methanolic solution of 53b in the presence of KOH resulted in hydrolysis of the dichloromethyl group and formation of aldehyde 54 (Scheme 26).…”
Section: Account Synlettmentioning
confidence: 95%
“…Reflux of a methanolic solution of 53b in the presence of KOH resulted in hydrolysis of the dichloromethyl group and formation of aldehyde 54 (Scheme 26). 40 Scheme 26 Synthesis of 54. Reagents and conditions: i, 1) MeOH, KOH, reflux, 2 h; 2) concd HCl.…”
Section: Account Synlettmentioning
confidence: 99%